Recurrence Risk and Prognostic Parameters in Stage I Rectal Cancers - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Background: The standard therapy for stage I rectum cancer is surgical resection. Currently, there is no strong evidence to suggest that any type of adjuvant therapy is beneficial. The risks of local relapse and distant metastasis are higher in rectal tumors. Therefore, while there is no clearly defined absolute indication for adjuvant therapy in lymph node negative colon cancers, rectum tumors that are T3N0 and higher require adjuvant treatment. Due to the more aggressive nature of rectal cancers, we explored the clinical and pathologic factors that could predict the risk of relapse in Stage I (T1-T2) disease and whether there was any progression-free survival benefit to adjuvant therapy. Materials and Methods: This multicenter study was carried out by the Anatolian Society of Medical Oncology. A total of 178 patients with rectal cancers who underwent curative surgery between January 1994 and August 2012 in 13 centers were included in the study. Patient demographics, including survival data and tumor characteristics were obtained from medical charts. Results: The median age was 58 years (range 26-85 years). Most tumors were well or moderately differentiated. For adjuvant treatment, 13 patients (7.3%) received radiotherapy alone, 12 patients (6.7%) received chemotherapy alone and 15 patients (8.4%) were given chemoradiotherapy. Median follow up was 29 months (3-225 months). Some 42 patients (23.6%) had relapse during follow up; 30 with local recurrence (71.4%) whereas 12 (28.6%) were distant metastases. Among the patients, 5-year DFS was 64% and OS was 82%. Mucinous histology and receiving adjuvant therapy were found to have statistically insignificant correlations with relapse and survival. Conclusions: In our retrospective analysis, approximately one quarter of patients exhibited either local or systemic relapse. The rates of relapse were slightly higher in the patients who had no adjuvant therapy. There may thus be a role for adjuvant therapy in high-risk stage I rectal tumors.
Keywords: Rectal cancer; adjuvant therapy; colon cancer; radiotherapy; prognosis; prognostic factors; TOTAL MESORECTAL EXCISION; LYMPH-NODE METASTASIS; TERM-FOLLOW-UP; LOCAL EXCISION; COLORECTAL-CANCER; RADIATION-THERAPY; ADENOCARCINOMA; CARCINOMA; COLON; EXPERIENCE